Glencoe world geography: a physical and cultural approach - Swanson, James L. (United States of America. McGraw-Hill School Publishing Company., 1992)
"Geography is the study of our physical environment and its impact upon our history and life-styles. By studying the geography of the earth and it's regions, we become better able to understand the nature of the world and the events that take place in it. We learn to deal more effectively with others because we are more capable of analyzing their needs and aims. For example, a knowledge of geography help us to determine why people in some lands are able are able to grow many kinds of food crops while people in other lands are not. Geography concepts and skills, moreover, help us to learn more about why we live and behave as we do. Geography helps to explain how our environment has affected us in the past and how it continues to affect us today. "
English text.
Keywords: World Geography